Modeling the Cost-Effectiveness of Home-Based HIV Testing and Education (HOPE) for Pregnant Women and Their Male Partners in Nyanza Province, Kenya. (1st August 2016) - Sharma, Monisha; Farquhar, Carey; Ying, Roger; Krakowiak, Daisy; Kinuthia, John; Osoti, Alfred; Asila, Victor; Gone, Molly; Mark, Jennifer; Barnabas, Ruanne V.
Abstract : Introduction: Women in sub-Saharan Africa face a 2-fold higher risk of HIV acquisition during pregnancy and postpartum and the majority do not know the HIV status of their male partner. Home-based couple HIV testing for pregnant women can reduce HIV transmission to women and infants while increasing antiretroviral therapy (ART) coverage in men. However, the cost-effectiveness of this program has not been evaluated. Methods: We modeled the health and economic impact of implementing a home-based partner education and HIV testing (HOPE) intervention for pregnant women and their male partners in a region of Western Kenya (formally Nyanza Province). We used data from the HOPE randomized clinical trial conducted in Kisumu, Kenya, to parameterize a mathematical model of HIV transmission. We conducted an in-country microcosting of the HOPE intervention (payer perspective) to estimate program costs as well as a lower cost scenario of task-shifting to community health workers. Results: The incremental cost of adding the HOPE intervention to standard antenatal care was 31–37 and 14–16 USD per couple tested with program and task-shifting costs, respectively. At 60% coverage of male partners, HOPE was projected to avert 6987 HIV infections and 2603 deaths in Nyanza province over 10 years with an incremental cost-effectiveness ratio (ICER) of 886 and 615 per disability-adjusted life year averted for the program and task-shifting scenario, respectively. ICERs were robust to changes in intervention coverage, effectiveness, and ART initiation and dropout rates. Conclusions: The HOPE intervention can moderately decrease HIV-associated morbidity and mortality by increasing ART coverage in male partners of pregnant women. ICERs fall below Kenya's per capita gross domestic product (1358) and are therefore considered cost-effective. Task-shifting to community health workers can increase intervention affordability and feasibility. Abstract : Supplemental Digital Content is Available in the Text.